Culture Independent Genomic Comparisons Reveal Environmental Adaptations for Altiarchaeales - Bird, Jordan T.; Baker, Brett J.; Probst, Alexander J.; Podar, Mircea; Lloyd, Karen G. (Frontiers in Microbiology, 2016)
The recently proposed candidatus order Altiarchaeales remains an uncultured archaeal lineage composed of genetically diverse, globally widespread organisms frequently observed in anoxic subsurface environments. In spite of 15 years of studies on the psychrophilic biofilm-producing Candidatus (Ca.) Altiarchaeum hamiconexum and its close relatives, very little is known about the phylogenetic and functional diversity of the widespread free-living marine members of this taxon. From methanogenic sediments in the White Oak River Estuary, NC, we sequenced a single cell amplified genome (SAG), WOR_SCG_SM1, and used it to identify and refine two high-quality genomes from metagenomes, WOR_79 and WOR_86-2, from the same site in a different year. These three genomic reconstructions form a monophyletic group which also includes three previously published genomes from metagenomes from terrestrial springs and a SAG from Sakinaw Lake in a group previously designated as pMC2A384. A synapomorphic mutation in the Altiarchaeales tRNA synthetase β subunit, pheT, causes the protein to be encoded as two subunits at distant loci. Consistent with the terrestrial spring clades, our estuarine genomes contain a near-complete autotrophic metabolism, H2 or CO as potential electron donors, a reductive acetyl-CoA pathway for carbon fixation, and methylotroph-like NADP(H)-dependent dehydrogenase. Phylogenies based on 16S rRNA genes and concatenated conserved proteins identify two distinct sub-clades of Altiarchaeales, Alti-1 populated by organisms from actively flowing springs, and Alti-2 which is more widespread, diverse, and not associated with visible mats. The core Alti-1 genome supports Alti-1 as adapted for the stream environment, with lipopolysaccharide production capacity, extracellular hami structures. The core Alti-2 genome members of this clade are free-living, with distinct mechanisms for energy maintenance, motility, osmoregulation, and sulfur redox reactions. These data suggest that hami structure found in Ca. A. hamiconexum are not present outside of stream-adapted Altiarchaeales. Unlike Ca. A. hamiconexum, these sedimentary organisms have membrane-bound coenzyme A disulfide reductases, which suggest they may use reduced sulfur compounds either as electron donors or defense against oxidative stress. Homologs to a Na+ transporter and membrane bound coenzyme A disulfide reductase that are unique to the brackish sediment Alti-2 genomes, could indicate adaptations to the estuarine, sulfur-rich environment.